2013
DOI: 10.1177/0954405413496095
|View full text |Cite
|
Sign up to set email alerts
|

Research on the machined surface integrity under combination of various inclination angles in multi-axis ball end milling

Abstract: It is well known that the multi-axis machining technology has been developed into a key technique applied in the manufacturing field. The machined surface integrity is one of the most important factors influencing the performance of the produced components. Hence, this research concentrated on the machined surface integrity induced by the multi-axis milling operation with different inclination angle combinations. In this research work, the cutting conditions of the conventional or up-milling process with tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…By comparing Sa and Rt values, it found that vertical upward is the optimal cutting path [25]. Chen et al [26] studied the effect of different angle combinations on the surface topography in multiaxis milling. Better surface roughness could be achieved when rotation angles are 0 (positive lead), 60 (combination of positive tilt and positive lead), 90 (positive tilt), and 330 (combination of negative tilt and positive lead).…”
Section: Appl Sci 2018 8 X For Peer Review 3 Of 18mentioning
confidence: 99%
“…By comparing Sa and Rt values, it found that vertical upward is the optimal cutting path [25]. Chen et al [26] studied the effect of different angle combinations on the surface topography in multiaxis milling. Better surface roughness could be achieved when rotation angles are 0 (positive lead), 60 (combination of positive tilt and positive lead), 90 (positive tilt), and 330 (combination of negative tilt and positive lead).…”
Section: Appl Sci 2018 8 X For Peer Review 3 Of 18mentioning
confidence: 99%
“…In another analogous approach, free-form tool paths were favoured with respect to machining time in three-axis mode, but parallel tool paths were found to offer better quality and accuracy in two-axis mode for complex free-form surfaces. 10 Influence of tool inclination angles (tilt and lead) with respect to the feed direction on surface roughness, micro-hardness and residual stress state was studied experimentally in Chen et al 11…”
Section: Introductionmentioning
confidence: 99%
“…5 Additionally, appropriate lubrication and inclination angles produce substantial benefit in terms of milling surface integrity. 6,7…”
Section: Introductionmentioning
confidence: 99%